Sex difference in the risk for exercise-induced albuminuria correlates with hemoglobin A1C and abnormal exercise ECG test findings - Brzezinski, Rafael Y. (Cardiovasc Diabetol, 2017)
BACKGROUND: Albuminuria is an established marker for endothelial dysfunction and cardiovascular risk in diabetes and prediabetes. Exercise induced albuminuria (EiA) appears earlier and may be a more sensitive biomarker for renal endothelial damage. We sought to examine the association between EiA, parameters of the metabolic syndrome, A1C levels, exercise ECG test results and sex related differences in a large cohort of healthy, pre-diabetic and diabetic subjects. METHODS: A total of 3029 participants from the Tel-Aviv Medical Center Inflammation Survey cohort (mean age 46 years, 73% men) were analyzed. Multiple physiologic and metabolic parameters including A1C were collected and albuminuria was measured in all subjects before and immediately after completing an exercise ECG test. RESULTS: Exercise increased urinary albumin to creatinine ratio (ΔEiA) by 2.8 (0–13.6) mg/g for median (IQR) compared to rest albuminuria (p < 0.001). An increase in ΔEiA was observed with accumulating parameters of the metabolic syndrome. ΔEiA showed significant interaction with sex and A1C levels; i.e. women with A1C > 6.5% had an increased risk of higher ΔEiA (p < 0.001). Using a cutoff of ΔEiA > 13 mg/g (top quartile) we found that women with ΔEiA > 13 mg/g were at greater risk for abnormal exercise ECG findings, (OR = 2.7, p = 0.001). CONCLUSION: Exercise promotes excessive urinary albumin excretion in dysmetabolic patients. In women, a significant correlation exists between ΔEiA and A1C levels. A cutoff of ΔEiA > 13 mg/g in women may be used to identify populations at risk for abnormal exercise ECG test findings and perhaps increased cardiovascular risk. Future studies will be needed to further validate the usefulness of ΔEiA as a biomarker for cardiovascular risk in women with and without diabetes.